Т. 10 : Мировые сношения и их средства; Промышленность и техника - Шмид М.; Мите А.; Шмюкер Д.; Мюнх А.; Мюллер К.; Тонндорф Э.; Ридля Р.; Леви М. Ф.; Гезехус Н. А. (1904, 1904)
Текст в русской дореформенной орфографии